2018
DOI: 10.2478/jtes-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Education for Sustainable Development in Namibia: School Teachers’ Perceptions and Teaching Practices

Abstract: Education for Sustainable Development (ESD) has been viewed as education that helps people develop the attitude, skills, and knowledge to make well-informed decisions for the benefit of the present and future generations. It aims at providing quality education through shared understanding and multi-disciplinary approaches in meeting the developmental and environmental apprehension for a sustainable future. Many theorists envisaged ESD as enhancing active involvement of learners both in school and out of school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 33 publications
4
103
1
4
Order By: Relevance
“…ESD teaching is implemented in different ways by teachers [59]. Even though there is now an increasing amount of work on ESD implementation, the instructional design in formal education settings developed is still not well understood (e.g., [2,14,[60][61][62][63][64][65]).…”
Section: Purpose and Aim Of The Studymentioning
confidence: 99%
“…ESD teaching is implemented in different ways by teachers [59]. Even though there is now an increasing amount of work on ESD implementation, the instructional design in formal education settings developed is still not well understood (e.g., [2,14,[60][61][62][63][64][65]).…”
Section: Purpose and Aim Of The Studymentioning
confidence: 99%
“…The results showed that the training course was an occasion for teachers to discuss different pedagogical approaches, teaching strategies, and practices in intercultural education. Findings provided evidence that the course succeeded in promoting the achievement of new contents and strategies related to migrant children's education, and enhanced critical reflections among participants [25,26].…”
Section: Discussionmentioning
confidence: 88%
“…Because of this, and in order to actively contribute to this strategy, education should guarantee that students acquire all the necessary theoretical and practical knowledge with the aim of boosting sustainable development [20]. Among other things, it has to promote sustainable life styles, human rights, gender equality, the culture of peace and non-violence, world citizenship, and the value of cultural diversity, as well as the contribution of education to development [3,21].…”
Section: Education and Dialogue: Key Elements For The Evolution And Dmentioning
confidence: 99%
“…The UNESCO Incheon Declaration and Framework for Action for the implementation of Sustainable Development Goal 4 highlights that people's educational process is lifelong and that it is geared at giving them the capacity to think and feel. Likewise, it upholds that all agents in a city contribute to education and culture, and thus favour human development [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation